Profitability of crop cultivation under different land tenurial arrangements in some selected sites of Bangladesh (Bangladesh Journal of Agricultural Research, 2015)
Proper land tenurial arrangements perceived as an important strategy for input use and agricultural production in utilization of land resource. Government of Bangladesh initiated due measures in this respect by formulating and declaring the land reform ordinance 1984.The main quest of this study is to identify the profitability of crop cultivation and factors influencing gross revenues in the variousl and tenurial arrangements under this land reform ordinance 1984. In search of this research question, a case study was conducted in two Upazilas (sub districts) of Bangladesh based on cross section data. This data were collected by purposive stratified sampling technique in the year 2013. Benefit cost ratio (BCR) was used to identify the profitability of crop cultivation under different land tenurial arrangements. Ordinary least square (OLS) regression method was used to identify the factors influencing gross revenues of the share cropped land of owner cum tenant farmers. This study reveals that the aspects of land reform ordinance have been implemented in output sharing aspect but not in input cost sharing aspect. Again BCR in leased land was higher than share cropped land. Moreover, regression analysis indicates that farm size had significant positive impact on gross revenues. The study holistically reveals that lease arrangements could be judged as a vital player to increase gross revenue as well as profit inshare cropped lands. DOI: http://dx.doi.org/10.3329/bjar.v39i3.21988 Bangladesh J. Agril. Res. 39(3): 447-460, September 2014